Ankylosing Spondylitis Diagnosed After Epidural Hematoma and Paraplegia: A Case Report - Şeniz AKÇAY YALBUZDAĞ; Asiye Mukaddes EROL; Canan ÇELİK and Sezin SOLUM (Archives of Rheumatology, 2014)
Ankylosing spondylitis is an inflammatory disease involving the axial spine. Ankylosing spondylitis may render the spine prone to trauma, which may cause serious neurological lesions. In this article, we report a 61-year-old male case diagnosed as ankylosing spondylitis after the development of paraplegia due to lumbar vertebral fracture and epidural hematoma. We aimed to emphasize that ankylosing spondylitis may be diagnosed tardily after severe complications of disease, and report the rehabilitation outcomes of the patient.